2021
DOI: 10.26710/jbsee.v7i2.1672
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CEO, Director and Executive compensation on the Firm Performance with Moderating Effect of Research & Development

Abstract: The aim of this article is to investigate the relationship between the CEO, Director and executives’ compensation on firm performance. Moreover research and development as moderator check the relation of R&D over firm performance and CEO, directors, executives’ compensation in an emerging Pakistan market. This research uses the GSEM approach for the problem of abnormality and homoscedastic arise the sample data collected from PSE 100 index non-financial list over the era of 2014-2019.The data collection sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…On the other hand, Al-Shammari (2021) documented a positive correlation between the remuneration of CEOs and the strategic risk of an enterprise. In contrast, Rehman et al (2021) found that executive compensation and company profitability are positively correlated. In addition, Ahamed (2022), Amewu and Alagidede (2021), Kayani and Gan (2022) on equity (ROE), and market value.…”
Section: Ciei Under Ifrsmentioning
confidence: 83%
See 1 more Smart Citation
“…On the other hand, Al-Shammari (2021) documented a positive correlation between the remuneration of CEOs and the strategic risk of an enterprise. In contrast, Rehman et al (2021) found that executive compensation and company profitability are positively correlated. In addition, Ahamed (2022), Amewu and Alagidede (2021), Kayani and Gan (2022) on equity (ROE), and market value.…”
Section: Ciei Under Ifrsmentioning
confidence: 83%
“…,Mehran et al (2022),Rehman et al (2021), andWang et al (2021) demonstrated that executive compensation is positively associated with FP as measured by the return on assets (ROA), return…”
mentioning
confidence: 99%
“…Previous empirical studies on the relationship between Executive Compensation and Firm Performance have continued to yield conflicting findings. While many of these studies have established a negative, weak and no relationship (Al-Azhary, 2022;Singh, 2021;Rath, 2020;Cieslak et al 2021;Jiang & Zhang, 2018;Olaniyi et al, 2017), others have established positive and strong relationship (Ahamed, 2022;Omamo et al, 2022;Al-Shammari, 2021;Ma, 2021;Rehman et al, 2021;Wu, 2021). Based on these conflicting findings, this study therefore becomes imperative to further interrogate the nature of direction of this relationship between executive compensation and firm performance of listed non-financial firms in Nigeria.…”
Section: Introductionmentioning
confidence: 90%
“…Various studies (Guay, 1999; Coles et al , 2006; Armstrong & Vashishtha, 2012;Olaniyi et al, 2017; Jiang & Zhang, 2018; Rath et al , 2020; Al-Shammari, 2021; Cieslak et al, 2021; Ma et al , 2021; Rehman et al, 2021; Singh et al , 2021; Wu, 2021; Ahamed, 2022; Al'azhary et al , 2022; Omamo et al , 2022; Mohammed et al , 2023) on executive reward of the CEOs have looked into the impact of CEO wealth incentives on risk taking. Although these studies provided evidence of a nexus between compensation and risk taking, the outcomes have lacked consensus on the direction, degree and significance of the relationship.…”
Section: Introductionmentioning
confidence: 99%